2020
DOI: 10.1038/s41598-020-62046-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional identity enhances aboveground productivity of a coastal saline meadow mediated by Tamarix chinensis in Laizhou Bay, China

Abstract: Research in recent decades has confirmed that biodiversity influences ecosystem productivity; however, the potential mechanisms regulating this process remain subject to controversy, due to variation across ecosystems. Here, the effects of biodiversity on ecosystem productivity were evaluated using three variables of biodiversity (taxonomic diversity, functional identity, and functional diversity) and surrounding environmental conditions in a coastal saline meadow located on the south coast of Laizhou Bay, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…When placing the selected predictors and the response variables in a multivariate context, we notice that the total aboveground biomass (TAGB) is indirectly influenced by the soil variables via their effects on plant height and basal area. Similar findings have been reported in other coastal wetland plant communities (Yi et al 2020) and tropical forests (Finegan et al 2015), including Amazon lowland habitat types with contrasting edaphic environments (Baraloto et al 2011), where forest biomass seems to be mostly driven by well‐coordinated changes in tree height and basal area across gradients of soil water availability (Hernández‐Calderón et al 2014). Although wood density (WD) has been claimed as an important parameter for the accurate estimation of forest biomass (Mitchard et al 2014), WD has an insignificant effect on TAGB, although plant communities strongly differ in WD values.…”
Section: Discussionsupporting
confidence: 80%
“…When placing the selected predictors and the response variables in a multivariate context, we notice that the total aboveground biomass (TAGB) is indirectly influenced by the soil variables via their effects on plant height and basal area. Similar findings have been reported in other coastal wetland plant communities (Yi et al 2020) and tropical forests (Finegan et al 2015), including Amazon lowland habitat types with contrasting edaphic environments (Baraloto et al 2011), where forest biomass seems to be mostly driven by well‐coordinated changes in tree height and basal area across gradients of soil water availability (Hernández‐Calderón et al 2014). Although wood density (WD) has been claimed as an important parameter for the accurate estimation of forest biomass (Mitchard et al 2014), WD has an insignificant effect on TAGB, although plant communities strongly differ in WD values.…”
Section: Discussionsupporting
confidence: 80%
“…Numerous studies have found that a variety of soil determinants change plant community diversity and have used the results to develop a series of predicting models ( Wubs and Bezemer, 2018 ; Yi et al., 2020 ). Our study integrated soil determinants into the SHI to quantify soil habitat conditions, which eliminated the determinants’ multicollinearity and improved the accuracy of the prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…In the Yellow River Delta, China's largest delta, wetland halophyte plants, especially T. chinensis, have developed widespread community patches and have made significant contributions to ecological functions due to their high salinity and waterlogging tolerance. Previous studies have reported that soil water, salinity, and nutrients significantly affect the T. chinensis plant community in the Yellow River Delta, but they only examined the influence of plant community diversity using a single soil index (Wu et al, 2020;Yang et al, 2021;Zhang et al, 2023). Therefore, they were unable to fully reflect the impact of the soil environment on T. chinensis plant community diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Response traits describe a plant's response to environmental change, while effect traits describe the effect of a plant on ecosystem functioning (Li et al, 2019). Functional diversity refers to the value, range, and distribution of functional traits in a specific ecosystem or to the components of biodiversity that have an impact on how an ecosystem operates or performs and are determined disproportionately by the specific traits (Yi et al, 2020). These traits mediate species' responses to environmental changes (Jesse et al, 2016); moreover, these changes point to mechanism alterations in ecosystem functioning and services (Nicola et al, 2021).…”
Section: Introductionmentioning
confidence: 99%